Red House, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Exterior view of a government building known as the "Red House" where the Trinidad and Tobago Parliament meets. It is surrounded by trees and other greenery and decorated with several Union Jack flags and red, white and blue banners. The Union Jack flag is the national flag of the United Kingdom and was the official flag of Trinidad and Tobago, an overseas British territory and crown colony at the time of this postcard, circa 1926. Postcard number 18.
Colour: Red, Blue, White, Green, Brown; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Arches--Trinidad and Tobago; Windows--Trinidad and Tobago; Towers--Trinidad and Tobago; Hedges--Trinidad and Tobago; Landscape architecture--Trinidad and Tobago; Flags--Trinidad and Tobago; [1926]; Parliament Building (Trinidad and Tobago); Red House, The (Trinidad and Tobago)